The enigmatic clock of dinoflagellates, is it unique? - Jadhav, Dinesh Balasaheb; Sriramkumar, Yoshita; Roy, Sougata (Frontiers in Microbiology, 2022)
Dinoflagellate clocks are unique as they show no resemblance to any known model eukaryotic or prokaryotic clock architecture. Dinoflagellates are unicellular, photosynthetic, primarily marine eukaryotes that are known for their unique biology and rhythmic physiology, photosynthesis being the most relevant one in this context. Their physiological rhythms are driven by an internal oscillator with unknownwhose molecular underpinnings are yet unknown. One of the primary reasons of slow progression of their molecular studies is their extremely large and repetitive genomes, which made them refractory to molecular studies. However, dinoflagellates being a major primary contributor to the global carbon cycle and oxygen levels comprehending their internal clock and its interaction with its physiology becomes a subject of utmost importance. The advent of high throughput Omics techniques changed the landscape by providing a giant headway to understand the molecular architecture and functioning of the dinoflagellate clocks and their regulation of physiology in dinoflagellates. We use these extensive databases to perform meta-analysis to reveal the status of clock components in dinoflagellates. In this paper, we will delve deep into the various “Omics” studies that catered to various breakthroughs in the field of circadian biology in these organisms that were not possible earlier. The overall inference from these omics studies points towards an uncommon eukaryotic clock model with a prospective lead to future studies to understand the evolution of clocks.